The contribution of Innovation to Economic Growth: An Econometric Study at the Firm Level - Hember, John tim (Université d'Ottawa | University of Ottawa, 2006)
This paper performs a firm-level econometrics study to determine the contribution of innovation to the economic growth of firms, and to determine whether that contribution varies across industry sectors. Based on review of prior research, of this study ar